Sperm count and spermatophore regeneration of the Indian white shrimp Penaeus indicus. - Magdugo, Rexie P. (Iloilo City College of Fisheries, University of the Philippines in the Visayas, 2010)
The study was composed of two phases : 1) determined the time for complete regeneration of sperm ; and 2) compared sperm counts in shrimps fed different diets. In Phase 1, results hsowed that sperm count did not vary significantly with size (body weight or carapace length) of the shrimp or ampoule location (right or left) in the same individual. Sperm counts range from 1.54-15.31x106 sperm cells/spermatophore. Time for regeneration was determined by manual removal of a spermatophore from an individual shrimp and monitored sperm count at the initial and then at 3, 6, 9, 12, and 18 days after extraction. Although sperm cells were present as early as Day 3, sperm count reached initial levels only at Day 18 after extraction. In Phase 2, P. indicus adults were allowed to molt and spermatophores were manually extracted 3 days post-molt. Individual were then fed the different test diets : a) SEAFDEC-formulatedpellets (SFP) ; b) SFP + fresh squid ; c) SFP + fresh annelids ; and d) SFP + fresh squid + fresh annelids. Sperm count was monitored again Day 18. Sperm counts of those fed SFP alone (3.37x106) and SFP + squid (2.41x106) were significantly lower than those fed SFP + squids + annelids (11.16x106); those fed SFP + annelids had sperm count similar to all other treatments. No significant difference (P>0.05) was found in the percentage of live (99.4%) and normal (99%) sperm among the test diets. The significant increase of the sperm count of shrimps fed combination of feeds suggests that the male reproductive performance is affected by the nutritional status of the animal.
Thesis (M. S. Fisheries - Fisheries Biology) - University of the Philippines in the Visayas, April 2010.
Keywords: sperm count; spermatophore; white shrimp